Penerapan Media Goggle Sites Dalam Pembelajaran Menulis Teks Deskriptif Tentang Upacara Adat Pada Siswa Kelas IX A SMP Negeri 2 Bantarkawung Tahun Ajaran 2022/2023 - Wati, Susi Guntari; Werdiningsih, Yuli Kurniati; Sunarya, Sunarya (JISABDA: Jurnal Ilmiah Sastra dan Bahasa Daerah, Serta Pengajarannya, 2023)
The background of this research is the low ability of class IX A student at SMP Negeri 02 Bantarkawung in writing descriptive text aboaut traditional ceremonies and delivering material that is still conventional and monotonous, so that learning becomes passive and boring. Seeing such conditions, it is necessary to strive for the application of interesting and appropriate learning media so that it can facilitate students in expressing their ideas, and feelings, especially in writing descriptive texts. Thus the formulation of the problem that can be taken in this study is how to apply Google Sites media in learning to write descriptive texts about traditional caremonies in class IX A students of SMP Negeri 02 Bantarkawung. In addition, there is a research objective is to describe the application of Google Sites media in learning to write descriptive texts about traditional ceremonies in class IX A students of SMP Negeri 02 Bantarkawung.This research is included in the descriptive qualitative research. Data collection techniques in this study used test techniques in the form of knowledge and skills aspect questions as well as non-test techniques in the form of questionnaires.The results of this study are that Google Sites media can be applied in learning to write descriptive texts about traditional ceremonies in class IX A students of SMP Negeri 02 Bantarkawung. These results can be proven by the average value of students who achieve 92 in terms of knowledge aspects with a total of 19 students who complete. Meanwhile, from the aspect of skills, an average score of 87 was obtained with a total of 19 students who passed. Â Â